Optical genome mapping and revisiting short-read genome sequencing data reveal previously overlooked structural variants disrupting retinal disease-associated genes - Farrar, Gwyneth (My University, 2023)
Purpose: Structural variants (SVs) play an important role in inherited retinal diseases (IRD). Although the identification of SVs significantly improved upon the availability of genome sequencing, it is expected that involvement of SVs in IRDs is higher than anticipated. We revisited short-read genome sequencing data to enhance the identification of gene-disruptive SVs. Methods: Optical genome mapping was performed to improve SV detection in short-read genome sequencing−negative cases. In addition, reanalysis of short-read genome sequencing data was performed to improve the interpretation of SVs and to re-establish SV prioritization criteria. Results: In a monoallelic USH2A case, optical genome mapping identified a pericentric inversion (173 megabase), with 1 breakpoint disrupting USH2A. Retrospectively, the variant could be observed in genome sequencing data but was previously deemed false positive. Reanalysis of short-read genome sequencing data (427 IRD cases) was performed which yielded 30 pathogenic SVs affecting, among other genes, USH2A (n = 15), PRPF31 (n = 3), and EYS (n = 2). Eight of these (>25%) were overlooked during previous analyses. Conclusion: Critical evaluation of our findings allowed us to re-establish and improve our SV prioritization and interpretation guidelines, which will prevent missing pathogenic events in future analyses. Our data suggest that more attention should be paid to SV interpretation and the current contribution of SVs in IRDs is still underestimated.
Keywords: Optical genome mapping; Structural variants (SVs); inherited retinal diseases (IRD).; Short-read genome sequencing; Next-generation sequencing